'I'm the Goshdarn Batman!' Affect and the aesthetics of cute superheroes. Issue 2 (4th March 2018) - Brown, Jeffrey A.
ABSTRACT: While contemporary superheroes are typically depicted in comic books and feature films as grim and gritty characters involved in violent adventures, the last decade has witnessed an increasingly prominent trend of cute superheroes emerging in popular culture. Infantile, Cherub-like cute superheroes circulate in comic books, animated video, toys and a range of merchandising products. The aesthetic of cute superheroes implies an inversion of the core attributes typically associated with superheroes: weak not strong, small not big, round not muscular, etc. The cute aesthetic inspires an effective response in readers/consumers of protectionism and possessability that reflects cultural beliefs about superheroes as symbolic of childhood innocence and play.